PENGARUH BUDAYA ORGANISASI, KOMITMEN PROFESI, DAN PERILAKU INOVATIF TERHADAP KEPUASAN KERJA GURU - Trie Utamy; I Made Murjana; Khaerul Hadi (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2024)
This study aims to examine the effect of organizational culture, professional commitment and innovative behavior on teacher job satisfaction at SMPN 7 Pujut in 2023. This research consists of 3 independent variables namely organizational culture (X1), professional commitment (X2) and innovative behavior (X3). and the dependent variable, namely job satisfaction (Y). The population in this study was 34 and the sample in this study was 34 respondents at SMPN 7 Pujut. Data was obtained by distributing 34 questionnaires and 36 statement items. Data were analyzed using SPSS 16.0. The results of this study indicate that organizational culture, professional commitment and innovative behavior have a significant effect partially, and simultaneously organizational culture, professional commitment and innovative behavior have a significant effect. The most dominant influencing variable is organizational culture with a regression value of 0.760.